Ghosts - Telgemeier, Raina (New York, NY Graphix, an imprint of Scholastic, 2016)
Catrina and her family have moved to the coast of Northern California for the sake of her little sister, Maya, who has cystic fibrosis--and Cat is even less happy about the move when she is told that her new town is inhabited by ghosts, and Maya sets her heart on meeting one
1 13
Keywords: Families -- California, Northern -- Comic books, strips, etc; Families -- California, Northern -- Juvenile fiction; Ghost stories; Ghosts -- Comic books, strips, etc; Moving, Household -- Comic books, strips, etc; Moving, Household -- Juvenile fiction; Sisters -- Comic books, strips, etc; Sisters -- Juvenile fiction; Cystic fibrosis -- Fiction; Family life -- California, Northern -- Fiction; Ghosts -- Fiction; Graphic novels; Moving, Household -- Fiction; Sisters -- Fiction; California, Northern -- Comic books, strips, etc; California, Northern -- Juvenile fiction; California, Northern -- Fiction